Local Policies in the Fight Against the Covid-19 Pandemic: Ankara and Rome Municipal Councils’ Decisions - Hicran Hamza Çelikyay; Hülya Küçük Bayraktar (Central European Public Administration Review)
Purpose and methodology: This study examines how the COVID-19 pandemic is included in municipal councils’ decisions and investigates the local policies developed through these decisions. Ankara and Rome Municipalities were selected as study samples. Turkey and Italy are both unitary states and their local government structures are similar because their local government systems are part of the Franco group, as defined by Hesse and Sharpe. Both cities have gained the status of metropolitan cities under the legal regulations adopted in recent years. For this reason, Ankara and Rome present similarities in terms of both the areas they serve and the responsibilities of being the capital. The decisions of their municipal councils were reviewed from March to December 2020. The decisions were analysed within the framework of the relevant commissions and application areas, and the local policies implemented in the fight against COVID-19 were put forward.